Effects of l-arginine and creatine administration on spatial memory in rats subjected to a chronic variable stress model. (August 2014) - dos Santos, Fabio Seidel; da Silva, Luiz Augusto; Pochapski, José Augusto; Raczenski, Alan; da Silva, Weber Claudio; Grassiolli, Sabrina; Malfatti, Carlos Ricardo Maneck
Abstract Context: Chronic stress results from repeated exposure to one or more types of stressors over a period, ranging from days to months, and can be associated with physical, behavioral, and neuropsychiatric manifestations. Some physiological alterations resulting from chronic stress can potentially cause deficits on spatial learning and memory. Objective: This study investigated the effects of chronic variable stress (CVS) and administration of l-arginine and creatine on spatial memory in rats. Furthermore, body, heart, adrenal weight, and plasma glucose and corticosterone levels were analyzed. Material and methods: Male Wistar rats were subjected to a CVS model for 40 days and evaluated for spatial memory after the stress period. Chronically stressed animals were treated daily by gavage with: 0.5% carboxymethylcellulose (Group Cs), 500 mg/kg l-arginine (Group Cs/La), 300 mg/kg creatine (Group Cs/Cr); and 500 mg/kg l-arginine and 300 mg/kg creatine (Group Cs/La + Cr) during the entire experimental period. Results: Our results showed that animals in the Cs/Cr and Cs/La + Cr groups presented significantly decreased corticosterone levels compared to group Cs (p < 0.05); animals in group Cs/Cr were more efficient in finding the platform, in the working memory task, compared to all other groups (p < 0.01); and animals in group Cs/La + Cr significantly improved in reference memory retention compared to controls (p < 0.05). Discussion and conclusion: Overall, these results demonstrated that a single administration of creatine improves working memory efficiency, and, when co-administrated with l-arginine, improves reference memory retention, a phenomenon that is possibly associated with increased creatine/phosphocreatine levels and l-arginine-derived NO synthesis.